1989
DOI: 10.1530/jrf.0.0850483
|View full text |Cite
|
Sign up to set email alerts
|

Cellular composition of the cyclic corpus luteum of the cow

Abstract: The cellular composition of CL from 6 cows on approximately Day 12 of the oestrous cycle, after synchronization with cloprostenol, was studied by ultrastructural morphometry. Point-count measurements of volume density (mean +/- s.d.) showed that large luteal cells occupied 40.2 +/- 7.0% of the luteal tissue, and small luteal cells 27.7 +/- 6.3%. Of the total of 393.4 +/- 52.0 x 10(3) cells per mm3 of luteal tissue, large luteal cells made up only 3.5% and small luteal cells 26.7%, a ratio of 1:7.6. Endothelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
136
0
6

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(145 citation statements)
references
References 5 publications
3
136
0
6
Order By: Relevance
“…Endothelial cells account for more than half the cells in the bovine CL (O'Shea et al 1989) and have been shown to express a non-genomic progesterone receptor (Falkenstein et al 1996). Thus, much/all of the binding to luteal membranes could be accounted for by contamination with endothelial cell membranes.…”
Section: Membrane Progesterone Receptors In Bovine Follicle Cellsmentioning
confidence: 99%
“…Endothelial cells account for more than half the cells in the bovine CL (O'Shea et al 1989) and have been shown to express a non-genomic progesterone receptor (Falkenstein et al 1996). Thus, much/all of the binding to luteal membranes could be accounted for by contamination with endothelial cell membranes.…”
Section: Membrane Progesterone Receptors In Bovine Follicle Cellsmentioning
confidence: 99%
“…Expression of class II MHC on macrophages is not surprising and would be expected. However, in midcycle (days 10-12) CL, staining was also observed on cells, whose distribution and architecture relative to the surrounding tissue were reminiscent of endothelial cells (Farin et al 1986, O'Shea et al 1989). In the second experiment, class II MHC was colocalized with a subpopulation of endothelial cells in the midcycle CL.…”
Section: Discussionmentioning
confidence: 99%
“…Bovine CL consists of various cell types including LCs, vascular endothelial cells, smooth muscle cells, fibroblasts, and immune cells (O'Shea et al 1989, Lei et al 1991, Zheng et al 1993, Penny 2000. Therefore, we first examined the mRNA expression of the lymphangiogenic factors in various cells, including LCs and LECs, isolated from the CL, LyECs isolated from the internal iliac lymphatic vessels, and PBMCs and PMNs isolated from peripheral blood (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The development of the bovine CL is accompanied by active angiogenesis, and the structure of blood vessels is retained during pregnancy (O'Shea et al 1989, Lei et al 1991, Beindorff et al 2010. Leukocytes, including monocytes/macrophages, granulocytes, and T lymphocytes, are localized to the CL in several species (Standaert et al 1991, Brannstrom et al 1994, Reibiger & Spanel-Borowski 2000.…”
Section: Introductionmentioning
confidence: 99%